Traumatismos bucomaxilofaciais em um hospital público do Brasil Central: estudo retrospectivo - Scartezini, Guilherme Romano (2013)
Aim: To evaluate epidemiological aspects of maxillofacial-oral injuries in hospitalized patients. Material and Methods: The sample was composed by 405 patients treated at the Department of Oral and Maxillofacial Surgery of the Emergency Hospital of Aparecida de Goiânia, Brazil, between 2011 and 2013. The following informations were collected from the patients’ medical records: gender, age, cause of injury, seasonal distribution, patient’s location and type of injury. The statistical treatment analyzed data from frequency distribution and chi-squared test. The level of significance was set at 5% for all analyses. Results: Higher occurrence of maxillofacial-oral injuries was observed in males (n=294; 72.59%), with 21-30 years old (n=106; 26.17%) and from the city of Aparecida de Goiânia. The main etiologic factors involved were vehicle traffic accidents (n=124; 30.62%), falls (n=92; 22.72%) and violence (n=87; 21.48%). The seasonal distribution showed that most cases occurred in autumn (n=154; 38.02%), followed by summer (n=138; 34.07%). The most common injuries were facial fractures (n = 324; 80.0%), the nasal bone, the most affected (n = 161; 39.75%) anatomical region. Statistically significant associations between etiological factor, gender and age (p <0.005) were observed. Conclusions: There were a high number of maxillofacial-oral injuries in males, aged less than 30 years old and due vehicle traffic accidents.